Development of a Differentiated Make a Match Model to Enhance Student Well-Being in Elementary School Students - Khodijah, Khodijah; Hartinah, Sitti; Habibi, Beni (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a differentiated Make a Match learning model to enhance the emotional and social well-being (student well-being) of elementary school students in Bumijawa Subdistrict, Tegal Regency. The research employs a Research and Development (RD) method with a mixed-methods approach, utilizing questionnaires, observations, and documentation as instruments. The model is designed to address issues in conventional learning, which tend to be less interactive, resulting in low student motivation and suboptimal social relationship building. The findings reveal that the differentiated Make a Match model effectively enhances student engagement, learning motivation, and positive relationships between students and teachers. This approach provides an inclusive learning experience by accommodating students' diverse needs and abilities. The study makes a significant contribution to supporting the implementation of the Merdeka Curriculum and fostering a holistic, student-centered learning environment.